2013
DOI: 10.1179/1743294413y.0000000111
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of low and atmospheric pressure air plasma treatment of polyethylene

Abstract: Surface activation of polyethylene (PE) samples has been carried out using low pressure plasmas (at two different operating frequencies, namely, 40 kHz and 13?56 MHz) and dielectric barrier discharge (DBD) (50 Hz frequency and at atmospheric pressure), and the results are compared. The surface of the PE samples has been exposed to these different plasmas for various time durations ranging from 1 to 30 min. The treated samples have also been studied for their aging behaviour by exposing them to the ambient atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 22 publications
1
14
0
7
Order By: Relevance
“…Similar results were observed by Švorčík et al (2007), who described after argon plasma exposure an increase in 3.02 nm LDPE sheet roughness [ 13 ]. Likewise, Kikani et al (2013) observed an increase in roughness values after submitting PE sheets to air plasma discharge, at low and high atmospheric pressures [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar results were observed by Švorčík et al (2007), who described after argon plasma exposure an increase in 3.02 nm LDPE sheet roughness [ 13 ]. Likewise, Kikani et al (2013) observed an increase in roughness values after submitting PE sheets to air plasma discharge, at low and high atmospheric pressures [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…ostreatus treatment. This rise is attributed to polar group formation, such as carbonyl (C = O), carboxyl (C = O-OH), and hydroxyl (-OH) [ 34 ], responsible for SCA decrease due to changes in superficial hydrophobicity [ 41 , 42 ]. After five-month biodeterioration curve (150 days), LDPE sheet CA for PBBT 150 sequential treatment was 17 ± 4 ° (p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both LP and AP plasmas were used to activate the polyethylene surfaces [20]. The influence of plasma process parameters, such as operating frequencies (40 kHz and 13.56 MHz at LP) and dielectric barrier discharge (50 Hz at AP), on the polymer surface activation were compared.…”
Section: Introductionmentioning
confidence: 99%